Beginning Teachers' Experiential Learning in the Era of Common Core: A Case Study (Journal of School Administration Research and Development, 2016)
This qualitative, single-case study described the professional learning experiences of a group of beginning teachers who participated in a California teacher induction program. The study contributes to an understanding of factors that form the foundation of professional learning as perceived by the participants. Furthermore, the study adds to extant literature on induction, including the transition period between pre-service and in-service phases, experiential learning throughout day-to-day events and action research undertook during inquiry-based projects. The following themes emerged from the study: transition from pre-service to induction, context for teaching and learning, collaboration with peers, subtle shift from content standards to Common Core standards, questioning and ascertaining the merits of inquiry as professional development, learning by experimentation and from life experiences, current practice as the ultimate payoff, nurturing experiential learning, obstacles to induction, and managing the 21st-century classroom. While beginning teachers perceived induction as one aspect of their professional learning, they deemed other factors, such as school climate, leadership, and bureaucracy as elements that could either advance or thwart their development.